Evaluation of pregnant women admitted with prelabour rupture of membranes (PROM) - Iloanusi, Nicholas Emeka (My University, 2013)
Background and objectives Prelabour rupture of the membranes (PROM) is a major obstetric problem affecting about 20% of pregnancies. Complications include preterm labour, ascending intrauterine and perinatal infections, and neonatal mortality. Standard guidelines are formulated and continually reviewed to improve the clinical management of PROM and to reduce poor perinatal outcomes associated with this condition. The objectives of this study, conducted using women in Johannesburg as a sample population, were: 1) to audit the implementation of the standard protocol on management of PROM, and 2) to determine the maternal and fetal outcomes of this condition. Methods A cross-sectional descriptive study was done on women admitted to the antenatal wards of Chris Hani Baragwanath Academic Hospital with PROM. Inclusion criteria were that PROM was the main reason for admission, gestation ≥24 weeks, and maternal age 18 years or more. Hospital clinical files were studied for obstetric and clinical characteristics, adherence by doctors to the management protocol, and final outcome including latency period, induction rate, mode of delivery, and neonatal outcome. Results Ninety-seven women participated in the study. Their mean age was 27.0 years, and 37 (38%) were nulliparous. Eighty-five (87%) had attended antenatal clinic. Twenty-nine (30%) were HIV-infected, 23 (79%) of them on highly active antiretroviral treatment. 6 The mean gestational age on admission was 32.8 weeks, with 78 (80%) women having preterm PROM at GA<37 weeks and 52 (54%) at GA <34 weeks. The most frequent methods of diagnosis were visual inspection in 77 (79%), speculum examination in 49 (51%) and ultrasound scan in 81 (84%) of the women. Antibiotics were given to 96 women (99%), and antenatal corticosteroids were used in all women <34 weeks pregnant. No cases of clinical chorioamnionitis were detected. The mean latency from PROM to delivery for women <37 weeks pregnant was 15 days, and for those <34 weeks, it was 19 days. Twenty-nine women (30%) required induction of labour, and 25 (25.8%) had caesarean sections. There were 12 perinatal deaths (with the exclusion of three late neonatal deaths), resulting from prematurity (n=4), congenital anomalies (n=2), neonatal jaundice (n=2), respiratory distress syndrome (n=2) and perinatal asphyxia / hypoxic ischaemic encephalopathy (n=2). There were no recorded cases of either neonatal or puerperal sepsis. Conclusion The study may have under-represented term PROM, so the findings are most applicable to preterm PROM. The condition was mostly managed appropriately within the local protocol, especially in terms of corticosteroid and antibiotic use. Overt or clinically evident chorioamnionitis was not detected. However, the perinatal mortality rate was high, and whatever the causes of perinatal death in this group, it is clear that PROM is a high-risk condition deserving of close clinical attention.
Department of Obstetrics and Gynaecology, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg
Keywords: Pregnancy Complications; Fetal Membranes, Premature Rupture